2001
DOI: 10.1148/radiographics.21.2.g01mr02451
|View full text |Cite
|
Sign up to set email alerts
|

Urachal Remnant Diseases: Spectrum of CT and US Findings

Abstract: Computed tomography (CT) and ultrasonography (US) are ideally suited for demonstrating urachal remnant diseases. A patent urachus is demonstrated at longitudinal US and occasionally at CT as a tubular connection between the anterosuperior aspect of the bladder and the umbilicus. An umbilical-urachal sinus manifests at US as a thickened tubular structure along the midline below the umbilicus. A vesicourachal diverticulum is usually discovered incidentally at axial CT, appearing as a midline cystic lesion just a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
304
0
18

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(322 citation statements)
references
References 43 publications
0
304
0
18
Order By: Relevance
“…However, a vestigial small lumen lined by a transitional epithelium is seen commonly in the fully developed infant [3] . Occasionally, the urachus may merge with one or both of the obliterated umbilical arteries, and there may be a slight deviation to the right or left of the mid line [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a vestigial small lumen lined by a transitional epithelium is seen commonly in the fully developed infant [3] . Occasionally, the urachus may merge with one or both of the obliterated umbilical arteries, and there may be a slight deviation to the right or left of the mid line [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Cilento et al [9] reported 45 UR excisions with three postoperative wound infections. Urachal anomalies are twice as common in men as those in women [4] , and are rarely observed in adulthood. Modes of presentation differ from those seen in children.…”
Section: Discussionmentioning
confidence: 99%
“…Most UC's are generally infected and the responsible microorganism is usually Staphylococcus aureus (47). Furthermore, infected UC can be radiologically mistaken for MD (48). But formation of enterocutaneous fistula from umbilicus after the penetration and perforation of MD into UC have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the anatomy and embryology of urachal cysts and remnants is critical in making the correct diagnosis and choosing an effective management strategy, which can avoid the complications of intraperitoneal rupture, or subsequent malignancy (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…However, persistence of an embryonic urachal remnant can give rise to various clinical problems, not only in infants and children but also in adults. Because urachal remnant anomalies are uncommon and manifest with nonspecific symptoms, definitive presurgical diagnosis is not easily made (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%